Risk of Obesity on Woman Health in Baghdad City - A. Fakhry, Faeza (Iraqi Journal of Science, 2021)
Maternal obesity is linked rates of high-risk obstetrical conditions such as diabetes and hypertension with higher rates of cesarean section. Pregnancy outcomes are negatively affected by maternal obesity (increased risk of neonatal mortality and malformations) . The research aims to show the effect of obesity of woman on physical and metabolisms status.